Expression, purification, and circular dichroism analysis of human CDK9 - Leopoldino, A. M.; Canduri, F.; Cabral, H.; Junqueira, M.; Marqui, A, B. T. de; Apponi, L. H.; da Fonseca, I. O.; Domont, G. B.; Santos, D. S.; Valentini, S.; Bonilla-Rodriguez, G. O.; Fossey, Marcelo Andrés [UNESP]; et al. (Elsevier B.V., 2006)
The human cyclin-dependent kinase 9 (CDK9) protein was expressed in E coli BL21 using the pET23a vector at 30 degrees C. Several milligrams of protein were purified from soluble fraction using ionic exchange and ATP-affinity chromatography. The structural quality of recombinant CDK9 and the estimation of its secondary structure were obtained by circular dichroism. Structural models of CDK9 presented 26% of helices in agreement with the spectra by circular dichroism analysis. This is the first report on human CDK9 expression in Escherichia coli and structure analysis and provides the first step for the development of CDK9 inhibitors. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: CDK9; Câncer; AIDS; Structure; dichroism analysis; molecular modeling; expression